Knowledge, attitude and preferences of pregnant women towards mode of delivery in a tertiary care center - Varghese, Shiny; Singh, Smita; Kour, Gagandeep; Dhar, Tapasya (International Journal of Research in Medical Sciences, 2016)
Background: Delivery mechanism is a spontaneous process and requires no intervention. Advances in medical technology in maternity care have drastically reduced maternal and infant mortality. Aim of the study was to determine maternal knowledge, attitude and preferences of pregnant women towards mode of delivery in a tertiary care center. Methods: This was a prospective study conducted on 100 antenatal women in third trimester who attended the antenatal clinic in Christian Medical College and Hospital, Ludhiana, Punjab from September 2015 to January 2016.The information regarding socio-demographic profile, obstetric history, knowledge and attitude statements towards vaginal and cesarean delivery was collected. Results: Total of 100 women was enrolled in the study. Out of these, majority (47%) had secondary education. Majority of the women (89%) interviewed had positive attitude towards vaginal delivery. High rate of cesarean section was seen in patients with primary and secondary infertility as they thought that babies born by cesarean section are healthier than those delivered by vaginal delivery. The most frequently mentioned source of information about mode of delivery was family and friends. Almost half of women agreed to the statement that vaginal delivery creates a more affectionate mother and baby relationship. Economic factors play an important role in deciding cesarean birth. Conclusions: Majority of pregnant women interviewed in our institution were keen to deliver vaginally, while the remaining women due to lack of knowledge or phobia of vaginal delivery wanted to undergo a cesarean section. Improving women’s knowledge about the risks and benefits of different modes of delivery can lead to a positive maternal attitude towards vaginal delivery.